Effect of Electron Beam Generated X-ray Pretreatment on Postharvest Storage Quality of the Mushroom Agaricus bisporus - CUI Yuan, ZHONG Yuanyuan, YU Jiangtao, BAI Junqing, MA Ji, LI Mei (Shipin Kexue)
This study investigated the effect of electron beam generated X-ray (EBGX) irradiation at different doses (0, 0.3, 0.6, 0.9 and 1.2 kGy) on the storage quality of harvested Agaricus bisporus at (15 ± 1) ℃. The results indicated that EBGX-treated mushroom had significant superiority in delaying mass loss, maintaining apparent color and textural properties, and promoting phenol accumulation compared with the non-treatment group. Different from the other irradiation doses, the 0.9 kGy treatment effectively delayed the rate of superoxide anion radical production, reduced the accumulation of reactive oxygen species (ROS), enhanced the activities of superoxide dismutase (SOD) and catalase (CAT), and inhibited microbial growth. It is suggested that EBGX treatment can obviously delay the quality deterioration of A. bisporus during storage. This study provides a theoretical basis for the application of EBGX treatment in the preservation of A. bisporus.